ANALISIS PERBANDINGAN RASIO KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH - Malik Madani; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis study aims to conduct the financial ratios of conventional banks and Islamic banks in the 2016-2018 period. The financial ratios used are Capital Adequacy (CAR), Return on Assets (ROA), Return on Equity (ROE), Beban Operasional terhadap Pendapatan Operasional (BOPO), Loan to Deposit Ratio (LDR), and Non Performing Loan (NPL).               The data used in this study are the financial statements of conventional banks and Islamic banks reported on the Indonesia Stock Exchange in the period 2014-2018. After passing through the purposive sample method, the eligible samples are 33 conventional banks and 3 Islamic banks.               The analysis technique used to see the comparison of financial ratios of conventional banks and Islamic banks is the Wilcoxon Signed Rank T-test method. The analysis conducted showed significant differences in Capital Adequacy (CAR),Return on Assets (ROA), Return on Equity (ROE), Beban Operasional terhadap Pendapatan Operasional (BOPO), Loan to Deposit Ratio (LDR), and Non Performing Loan (NPL). Keywords: Comparative Analysis of Conventional Financial Ratios of Banks and Islamic Banks, Wilcoxon Signed Rank T-test.